Contrasting Capitalist and Sharia Economic Systems: A Comparative Inquiry into Core Economic Values - Hafidz, Dzarin Gifarian Khaulani (Islamicate Institute, 2024)
This study offers a comparative analysis of the ethical, institutional, and distributive foundations of capitalist and Sharia economic systems. While capitalism emphasizes market efficiency, individual freedom, and profit maximization, Sharia economics prioritizes divine accountability, social equity, and moral purpose. Drawing on conceptual literature and policy analysis, the research highlights the divergent ethical logics, governance mechanisms, and wealth distribution strategies of each system. Capitalist institutions reward market productivity but often generate inequality and value-neutral governance. In contrast, Sharia-based institutions operationalize justice through instruments such as zakat, waqf, and profit-sharing contracts, embedding ethics into economic life. The study contributes a refined framework for evaluating economic systems based on values and justice, offering both theoretical insights and practical implications for policy and development. This research underscores the urgency of rethinking global economic models in an era of deepening inequality and ethical fragmentation.